The haunted wilderness : the gothic and grotesque in Canadian fiction - Northey, Margot, 1940- (Heritage., 1976)
By analysing a number of Canadian works of fiction from the nineteenth century to the present, Margot Northey demonstrates that Gothicism, in varying degrees and of various kinds, has been a continuing feature of our fiction.